Switchable Synthesis of Sulfoxides, Sulfones and Thiosulfonates through Selectfluor-Promoted Oxidation with H2O as O-Source - Guo, Xuqiang; Sun, Xuejun; Jiang, Mengmeng; Zhao, Yulei (Synthesis, 2022)
A practical and efficient protocol for the switchable synthesis of sulfoxides, sulfones, and thiosulfonates via Selectfluor-mediated oxidation of sulfides and thiols, respectively, at ambient temperature has been developed. All these organosulfur compounds can be prepared with nearly quantitative yields by applying eco-friendly H2O as O-source. The formation of sulfoxides and thiosulfonates takes only a few minutes (3–20 min). As suggested by the control experiments, the oxidation procedure might proceed through the fluorination of sulfide, nucleophilic addition with H2O, and elimination of hydrogen fluoride.
Keywords: oxidation; sulfoxides; sulfones; thiosulfonates; Selectfluor